Spain and Italy Experience of Digital Education and E-Learning during the Pandemic - Beletskaya, O.S.; Eranova, N.A.; Kucheryavenko, V.V. (Âzyk i tekst, 2020)
Abstract only Due to the threat of the novel coronavirus infection, most schools, colleges and universities in Italy and Spain followed the recommendation of the Ministries of Science and Healthcare and opted to shift to distance learning mode. Needless to say, that fact had an impact on how the educational process was organized changed the format of communication and implementation of curricula and syllabi. The relevance of this study is conditioned by a growing interest to the problems of distance learning during the pandemic and the scarce research into this subject. The purpose of this paper is to identify and describe computer technologies applied in distance learning in educational institutions of Spain and Italy over the pandemic period. As part of research, we analyzed the data provided by the Spanish and Italian Ministries of Education and Science, as well as over 50 articles published by leading Spanish and Italian printed media, such as Corriere, Repubblica, Ilfattoquotidiano, Varesenews, Agi, OrizzonteScuolat, Udinetoday, El Pais, Expansion, ABC, El Tiempo, etc. The theoretical underpinning for the study is comprised of papers by distance learning experts: I.K. Korneyev, G.N. Ksandopulo, V.A. Mashurtsev [2009], V.L. Uskov [2008], Sharples M., Adams A., Alozie N., Ferguson R., FitzGerald E., Gaved M., McAndrew P., Means B., Remold [2015], Gros B. [2016], Bates A. [2015]. Из-за угрозы заражения новым коронавирусом большинство школ, колледжей и университетов в Италии и Испании последовали рекомендации министерств науки и здравоохранения и решили перейти в режим дистанционного обучения. Само собой разумеется, что этот факт повлиял на то, как был организован учебный процесс, изменил формат общения и реализации учебных планов и программ. Актуальность данного исследования обусловлена растущим интересом к проблемам дистанционного обучения в период пандемии и скудностью исследований по этой теме. Целью данной статьи является выявление и описание компьютерных технологий, применяемых в дистанционном обучении в учебных заведениях Испании и Италии в период пандемии. В рамках исследования мы проанализировали данные, предоставленные министерствами образования и науки Испании и Италии, а также более 50 статей, опубликованных ведущими испанскими и итальянскими печатными СМИ, такими как Corriere, Repubblica, Ilfattoquotidiano, Varesenews, Agi, OrizzonteScuolat, Udinetoday, El Pais, Expansion, ABC, El Tiempo и т.д. Теоретическую основу исследования составили статьи экспертов по дистанционному обучению: И.К. Корнеев, Г. Ксандопуло, В.А. Машурцев [2009], В.Л. Усков [2008], Шарплс М., Адамс А., Алози Н., Фергюсон Р., Фицджеральд Э., Гавед М., МакЭндрю П., Средство Б., Ремольд [2015], Грос Б. [2016], Бейтс А. [2015].